2022
DOI: 10.1093/fampra/cmac138
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the 2019/20 bushfires and COVID-19 pandemic on the physical and mental health of older Australians: a cross-sectional survey

Abstract: Background In 2019/20 major bushfires devastated Australia’s East Coast. Shortly afterward the COVID-19 pandemic was declared. Older people are disproportionately affected by disasters and are at high risk from respiratory pandemics. However, little is known about how these events impact on older peoples’ health and well-being and engagement with services such as primary care. Objective To explore the health impacts of the 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The ImPress study Due to the impacts of disaster and COVID-19, 15,16 the sample size was smaller than the intended full trial.…”
Section: Impact Of a General Practice Nurse Intervention To Improve B...mentioning
confidence: 99%
“…The ImPress study Due to the impacts of disaster and COVID-19, 15,16 the sample size was smaller than the intended full trial.…”
Section: Impact Of a General Practice Nurse Intervention To Improve B...mentioning
confidence: 99%
“…Increased occurrence of extreme weather events caused by climate change results in poor health outcomes, especially in vulnerable populations (Foo, 2016; World Health Organization, 2021). In Australia, for example, frequent bushfires and floods adversely impact people's health, including exacerbated cardiorespiratory diseases, infectious diseases, and mental health issues (Black Dog Institute, 2021; Halcomb et al., 2022; McMichael et al., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…15 Cross-sectional surveys also indicate that bushfire and pandemic impacts are both associated with reduced mental health 11 and well-being 13 (although links with pandemic stressors may be attenuated when controlling for factors such as financial difficulties), 12 as well as greater social isolation. 14 By contrast, relevant studies have found no evidence of interactions between pandemic and bushfire impacts, although complex relationships have been observed with adverse childhood experiences (suggesting compounding effects of disasters and earlier trauma histories). 11 Fewer studies still have used qualitative designs to generate deeper understandings of the impacts of bushfires and the pandemic, and these have focused narrowly on experiences of loneliness and social isolation in the context of pandemic restrictions 16 and experiences of persons with specific health conditions such as multiple sclerosis.…”
mentioning
confidence: 97%
“… 15 Cross-sectional surveys also indicate that bushfire and pandemic impacts are both associated with reduced mental health 11 and well-being 13 (although links with pandemic stressors may be attenuated when controlling for factors such as financial difficulties), 12 as well as greater social isolation. 14 By contrast, relevant studies have found no evidence of interactions between pandemic and bushfire impacts, although complex relationships have been observed with adverse childhood experiences (suggesting compounding effects of disasters and earlier trauma histories). 11 …”
mentioning
confidence: 97%
See 1 more Smart Citation